Cold atmospheric plasma-aerosol treatment of equine dermatophytosis: a novel therapeutic approach - Kurras, Sandra; Knottenbelt, Derek; Schmelz, Ulrich; Schaal, Tom; Tischendorf, Tim; Fuchs, Robert; Schorling, Timon; Koene, Marc H. W. (Frontiers in Veterinary Science, 2025)
IntroductionDermatophytosis is a common fungal skin infection in horses, particularly affecting young and immunocompromised animals. Traditional treatments often involve antifungal medications with potential side effects. Here, we present a case report that evaluated the efficacy of cold atmospheric plasma-aerosol (CAP-A) as a standalone treatment for equine dermatophytosis.MethodsA 2-year-old Westphalian warmblood stallion presented with confirmed dermatophyte lesions restricted to the left side of the mouth which were treated with CAP-A. Treatment was administered 2 times daily for 12 consecutive days; each session consisted of two 3-min fogging cycles. Microbiological samples were collected before and after the treatment period. Daily photographic documentation was maintained.ResultsInitial microbiological examination identified Trichophyton ssp. (Trichophyton mentagrophytes, Trichophyton benhamiae, Trichphyton erinacei, Trichophyton tonsurans, Trichophyton equinum, Trichophyton verrucosum, or Trichophyton rubrum) as the definitive aetiology. Post-treatment samples were negative for all of the tested dermatophytes including Trichophyton spp., Microsporum canis, and Nannizzia ssp. Clinical progression was documented through photographic evidence. The horse showed no signs of discomfort during or after the treatment sessions.DiscussionCAP-A therapy demonstrated promising results as a non-pharmacological treatment option for equine dermatophytosis, achieving both clinical and microbiological resolution without adverse effects. This single case report will need to be followed up by a prospective study in a larger sample to draw definite conclusions about the efficacy of the treatment.